The Effect of the Green Shipping Campaign and Greenhouse Gas Emission Reduction Policy on Electric Vessel Procurement Mediated by Shipowner Perceptions: A Case Study at PT Pertamina Trans Kontinental (2025) - Parabil Matagiwa; Lira Agusinta; Juliater Simarmata (Dinasti Publisher, 2025)
Maritime transportation activities contribute to Greenhouse Gas (GHG) emissions. IMO adopted MARPOL Annex VI to prevent air pollution from ships. Several countries in the world have initiated the use of electric ships as a form of campaign. The Indonesian government also shows its commitment to reducing GHG emissions and encourages the use of electric transportation in the transportation sector. The government issued various policies supporting the use of electric transportation. However, electric transportation in Indonesia is still dominated by the land sector. The adoption of electric ships for some shipowners is still only a discourse that has not been realized, one of which is PT Pertamina Trans Kontinental (PTK). This study aims to analyze the influence of green shipping campaigns and GHG emission reduction policies on the procurement of electric ships mediated by shipowner perceptions. The method used is mixed methods with PLS-SEM analysis to 97 respondents followed by interviews with 5 informants determined by purposive sampling. The results show that green shipping campaigns have a significant effect on shipowner perceptions, and GHG emission policies have a significant effect on the procurement of electric ships. However, the relationship between green shipping campaigns and ship procurement and GHG reduction policies on perceptions is equally insignificant. Shipowner perceptions significantly mediated the effect of campaigns on electric ship procurement, but not the effect of GHG emission reduction policies. The implementation of electric ships in PTK is hampered by technical, operational, economic, regulatory, and sustainability awareness factors.